HUBUNGAN LAMA KERJA DAN MASA KERJA DENGAN NEUROPATI PERIFER PADA SUPIR ANGKUTAN KOTA TRAYEK 95 DI KOTA MEDAN TAHUN 2015 - wahyu eko syahputra; halinda sari lubis; isyatun mardiyah syahri (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Peripheral neuropathy is disorder in the edge or periphery of nerve which can cause symptoms such as the feeling of inflammation, cold pain, electric shock, prickling sensation in a part of the body, pain as if pierced by needles, numb, and itchy. One of the causes of peripheral neuropathy is the shaking from the seats and steering wheels. Not only will the work comfort and fatigue of workers who are exposed to this shaking be disturbed but they can also be detrimental to peripheral neuropathic. The research was an analytic survey with cross sectional design. The data were analyzed by using univatriate analysis and bivatriate analysis with chi square test. The population was 40 drivers of urban transportation line 95 in Medan, and all of them were used as the samples, using total sampling technique. The result of the research showed that the variable of work period was p > 0.05 which indicated that there was no correlation between the length of service and the incidence of peripheral neuropathic in the respondents, in 2015. The variable of the length of service was p < 0.05 which indicated that there was the correlation between the length of service and the incidence of peripheral neuropathic in the respondents, in 2015. The shaking measurement of the drivers’ seats was 118.64 µm and of the drivers’ steering wheels was 87.065 µm. According to the Decree of the Minister of State for Environment No. 49/1996, this shaking could arouse uncomfortable reaction to workers. Peripheral neuropathic can disturb one’s quality of life and work comfort. The best way to solve it is by controlling the shaking by changing the thin out seat cushions to the thicker ones, using shock absorber devices and standard suspension in order to lessen the buses’ shaking mechanism and to keep the machines in good condition.